The effect of research activities on nest predation in the Eurasian Reed Warbler Acrocephalus scirpaceus - J. Płóciennik; B. Czyż; L. Hałupka (The European Zoological Journal)
During studies of avian breeding biology, ecology and population dynamics, researchers have to breach nesting territories, which can potentially lead to various disturbances resulting in altered relationships in the predator-prey system. It is usually assumed that human disturbance reduces nest success in birds. However, recent studies have revealed that in most passerines there is no significant effect of human presence on nesting success. Moreover, some research even suggests that birds may benefit from researcher disturbance near nests. Here, we examine the effect of research activities on nest predation in a small reed-nesting passerine, the Eurasian Reed Warbler, studied during two consecutive breeding seasons. The study plot consisted of two adjacent parts (subplots) differing in the frequency of visits. In the second breeding season subplots were inverted (high-pressure subplot became a low-pressure subplot) to minimise the effect of external factors on the studied parameters. We observed some variability in predation rates between two breeding seasons, but the differences were not statistically significant. We also did not find significant differences in nest survival probabilities between subplots differing in human pressure neither at the egg nor at the nestling stage. We conclude that the researcher presence does not affect nest predation rates in the study population of Eurasian Reed Warblers.